Long-term follow-up of aneurysms treated electively with woven stent-assisted coiling. (15th December 2017) - Cheung, Nicholas K; Chiu, Albert HY; Cheung, Andrew K; Wenderoth, Jason D
Abstract : Background: Preliminary short-term results for stent-assisted coil embolization (SACE) using woven/braided stents have been promising. However, evidence supporting mid- to long-term efficacy and durability is lacking. Objective: To report the long-term results for the durability of elective intracranial aneurysms treated with woven stents. Materials and methods: Between May 2012 and May 2015, 98 consecutive patients with 103 aneurysms underwent elective woven SACE across three Australian neurovascular centres. All patients had immediate, 6- and 18-month clinical and radiological follow-up. Radiological assessment was performed with modified Raymond–Roy occlusion scores based on angiography results, while clinical assessment was based on the modified Rankin Scale. Results: Six-month follow-up was available in 100 aneurysms, and an 18-month follow-up in 97 aneurysms. Total occlusion rates of 82% were achieved at inception, 82% at 6 months, and 90% at 18 months. Satisfactory occlusion with small neck remnants was present in 17% at inception, 16% at 6 months, and 9% at 18 months. Good neurological outcomes were achieved in 95% at 18 months. Intraprocedural thromboembolic events were recorded in 3% and delayed events in 1% (all in patients taking clopidogrel). Aneurysm recurrence occurred in one patient (1%). Technical complications occurred in 5%. The total complication rate was 10%. Conclusions: Woven SACE is safe, efficacious, and durable at long-term 18-month follow-up, with very low recurrence and re-treatment rates. Preliminary results appear better than those for traditional laser-cut stents.